Pemberdayaan Masyarakat dan Pengelolaan Sampah Ramah Lingkungan melalui Sosialisasi dan Pelatihan Pembuatan Lilin Aromaterapi dari Minyak Jelantah - Nimah, Nuzulun (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Used cooking oil waste is one of the most common environmental problems found in communities, particularly in rural areas such as Wateskroyo Village. Improper disposal can pollute the environment and pose health risks. This program aims to empower the local community through a training on how to make aromatherapy candles from used cooking oil, serving as a waste management strategy and a means of creating new economic opportunities. Using the Asset-Based Community Development (ABCD) approach, the program began with education on the hazards of waste oil and its economic potential, followed by hands-on training. The results showed increased knowledge and skills among participants, along with a growing awareness and interest in environmentally friendly micro-enterprises. Despite challenges such as the limited availability of stearin, the program proved effective in encouraging community participation in creating eco-friendly and economically valuable local solutions. Therefore, this training contributes to community empowerment and sustainable development in Wateskroyo Village. Keyword: used cooking oil, aromatherapy candles, empowerment, environment